Research Trends of Coronavirus: Bibliometric Analysis from 1989-2019 - Singh, Shiv; Kataria, Sanjay; Dey, Tulika (International Journal of Knowledge Content Development & Technology, 2021)
The world is going through the most unprecedented time with the outbreak of novel Coronavirus disease (COVID-19), which has become a threat to millions. Coronavirus are a group of viruses that cause a variety of diseases in mammals and birds leading to a range of illnesses in humans including common cold and more severe forms like severe acute respiratory syndrome Coronavirus (SARS-CoV), Middle East respiratory syndrome Coronavirus (MERS-CoV) and COVID-19, which are life-threatening. The virus gets its name from its shape which takes the form of a crown with protrusions around it. In December 2019, a pneumonia outbreak was reported in Wuhan City of China, which was later traced to a novel strain of Coronavirus and termed as Novel COVID-19. It typically causes flu-like symptoms including fever, cough and shortness of breath and is transmitted through human-to-human and there is no cure of it till now. Thus, this bibliometric study has been carried out to analyse the research progress in Coronavirus and literature published during a period of 30 years (1989-2019). Data for the study were fetched from Web of Science(WoS) multidisciplinary database and the publication trends in terms of total articles, productive countries, institutions, journals, productive authors, most cited articles and authors, etc have been analysed. In total, 4917 articles were retrieved; these were from 711 sources and were contributed by 14442 authors. The collaboration index was 3.11, which clearly indicates that there has been a lot of collaboration in this field. The most preferred journal for the study period was “Journal of Virology” and maximum contribution has been from the University of Hong Kong.